2023
DOI: 10.1177/10870547221146244
|View full text |Cite
|
Sign up to set email alerts
|

A Critical View on Motor-based Interventions to Improve Motor Skill Performance in Children With ADHD: A Systematic Review and Meta-analysis

Abstract: Objective: To map the effect of motor-based interventions on motor skills in children with ADHD. Method: A systematic literature search was performed in Pubmed, Web of Science, and the SCOPUS database (last search: October 30th 2022). Methodological quality was assessed using the PEDro-scale and the quality of evidence was determined with the GRADE-method. Meta-analysis was performed when at least five studies were available. Results: Thirteen studies (7 RCTs) satisfied the inclusion criteria, five of which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 72 publications
1
6
0
Order By: Relevance
“…Fine motor PC was loaded by scores on Visuomotor Precision of NEPSY-II and MABC2 Manual Dexterity, which included tasks such as pegboard, lacing blocks, nuts and bolts, and tracing tasks. Our findings differ from Biscaldi et al (2015), which showed no difference in pegboard test between ADHD children and TD peers, but are in line with earlier studies consistently reporting fine motor difficulties in school-aged ADHD children, especially in tracing/ drawing tests (e.g., Goulardins et al, 2017;Kleeren et al, 2023). With this regard, previous research has indicated that difficulties in fine motor control could be related to core ADHD characteristics, such as difficulty in inhibiting prepotent responses (Kaiser et al, 2015).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Fine motor PC was loaded by scores on Visuomotor Precision of NEPSY-II and MABC2 Manual Dexterity, which included tasks such as pegboard, lacing blocks, nuts and bolts, and tracing tasks. Our findings differ from Biscaldi et al (2015), which showed no difference in pegboard test between ADHD children and TD peers, but are in line with earlier studies consistently reporting fine motor difficulties in school-aged ADHD children, especially in tracing/ drawing tests (e.g., Goulardins et al, 2017;Kleeren et al, 2023). With this regard, previous research has indicated that difficulties in fine motor control could be related to core ADHD characteristics, such as difficulty in inhibiting prepotent responses (Kaiser et al, 2015).…”
Section: Discussionsupporting
confidence: 88%
“…Previous works have formerly indicated that the motor skills of school‐aged autistic children could benefit from the reduction of the visual information speed and the concurrent increase of proprioceptive feedback (e.g., see Lidstone & Mostofsky, 2021). Concerning ADHD, our findings related to fine‐motor control difficulties highlight the potential of including training programs focused on executive functions, (such as inhibition and self‐monitoring) into standard motor‐based interventions (e.g., see Kleeren et al, 2023), given the potential role of these functions in tasks such as drawing and tracing. A strength of this study is the use of a multimodal approach to determine the specificity of motor difficulties in autism and ADHD.…”
Section: Discussionmentioning
confidence: 68%
“…This view is supported by meta-analysis showing that motor intervention provides the most promising treatment effects for improving motor skill relative to non-motor interventions (including medication; Kleeren et al, 2023).…”
Section: Discussionmentioning
confidence: 94%
“…Second, it indicates that standard treatments that address core ADHD symptoms may have limited impact on the motor symptoms of those with co‐occurring ADHD and DCD. This view is supported by meta‐analysis showing that motor intervention provides the most promising treatment effects for improving motor skill relative to non‐motor interventions (including medication; Kleeren et al, 2023 ).…”
Section: Discussionmentioning
confidence: 95%
“…However, medication treatment may be accompanied by side effects such as headaches, stomach pain, and decreased appetite (Pang and Sareen, 2021). Because of the potential side effects associated with medication treatment, nonpharmacological treatments with relatively lower side effects have developed rapidly in recent years (Cortese et al, 2022), such as physical activity interventions (Kleeren et al, 2023), neurofeedback interventions (Garcia Pimenta et al, 2021), and cognitive interventions (Pauli-Pott et al, 2021). Among them, physical activity interventions have become widely used nonpharmacological interventions due to their low cost, ease of operation, improvement of physical fitness, and long-lasting benefits including the acquisition of sports skills such as baseball techniques, equestrianism, basketball techniques, improvements in physical qualities such as strength, speed, flexibility, as well as a reduction in psychological issues and behavioral problems such as depression, anxiety, hyperactivity, and impulsivity (Kandola et al, 2019;Li et al, 2023a;Kleeren et al, 2023).…”
Section: Introductionmentioning
confidence: 99%